A developmentally regulated and tissue-dependent transcription factor complexes with the retinoblastoma gene product. - Partridge, J F (1991)
DRTF1 is a cellular transcription factor which complexes with the retinoblastoma (Rb) gene product and cyclin A, an association modulated by certain viral oncogenes, such as adenovirus E1a. Complexed DRTF1, referred to as DRTF1a, has similar DNA binding specificity and DNA binding polypeptides to DRTF1b, which lacks Rb. DRTF1b is abundant in both F9 embryonal carcinoma (EC) stem cells and pluripotent embryonic stem (ES) cells and is strongly down-regulated during the differentiation of both cell types, suggestive of a stem cell E1a-like activity. In contrast, DRTF1a, which in F9 EC cells is much less abundant than the other activities, is induced as F9 cells begin to differentiate. Consistent with the relationship between EC, ES and inner cell mass cells, DRTF1b is present in blastocyst stage embryos although as embryogenesis progresses the levels of Rb-complexed DRTF1 increase. Certain tissues, such as liver and brain, contain high levels of DRTF1 during early embryonic stages but little in adult terminally differentiated tissue, in contrast to the thymus, which contains high levels of Rb-complexed DRTF1 but lacks associated cyclin A. These data show that DRTF1 is a group of transcription factors that share common DNA binding polypeptides and which complex with other non-DNA binding proteins, such as the Rb protein and cyclin A, in a developmentally regulated and tissue-dependent fashion.